2021
DOI: 10.1101/2021.02.18.431426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain endothelial CXCL12 attracts protective Natural Killer cells during ischemic stroke

Abstract: Innate lymphoid cells (ILCs) have a function in homeostasis and immune responses, but their role in ischemic brain insult is unknown. Here, we report that ILCs are not resident within the brain parenchyma during steady-state conditions, but are attracted after ischemic stroke. Specifically, we identified NK cells, ILC1s, ILC2s and ILC3s within the lesion, the highest influx being observed for NK cells and ILC1s. We further show that Cxcl12 expressed at the blood-brain barrier is essential for NK cells and NKp4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Whether the CD49a + CD49b + Eomes − intILC1s are unique meningeal resident cells and are functionally different remains unknown. Both NKs and ILC1s have been observed within the meninges during steady-state conditions ( 3 , 38 , 42 , 43 ) ( Figure 1 ). Moreover, these two populations recirculate through peripheral lymphoid tissues ( 35 ), raising the question whether NKs and ILC1s within the meninges are migratory or resident.…”
Section: Ilcs In the Cns At Steady-statementioning
confidence: 99%
See 4 more Smart Citations
“…Whether the CD49a + CD49b + Eomes − intILC1s are unique meningeal resident cells and are functionally different remains unknown. Both NKs and ILC1s have been observed within the meninges during steady-state conditions ( 3 , 38 , 42 , 43 ) ( Figure 1 ). Moreover, these two populations recirculate through peripheral lymphoid tissues ( 35 ), raising the question whether NKs and ILC1s within the meninges are migratory or resident.…”
Section: Ilcs In the Cns At Steady-statementioning
confidence: 99%
“…Innate and adaptive immune cells including microglia, neutrophils, monocytes and lymphocytes play multiphasic roles in ischemic stroke and impact the pathogenesis of ischemic brain injury ( 70 – 73 ). NK cells have been detected in the brain parenchyma of stroke patients and mouse models with induced ischemic stroke ( 43 , 74 , 75 ). We observed that the robust accumulation of NK cells in the stroke lesion is caused by progressive migration rather than in situ proliferation ( 43 ).…”
Section: Ilcs In Neurological Diseasesmentioning
confidence: 99%
See 3 more Smart Citations